Macrophage polarization in disease therapy: insights from astragaloside IV and cycloastragenol - Xiong, Bei-Bei; Zhuo, Yu-Mei; Wang, Huan; Zheng, Qiao-Ling; Tang, Feng; Huang, Qun; Yao, Man (Frontiers in Pharmacology, 2025)
Dysregulated activation and polarization of macrophages drive the pathogenesis of diverse diseases, including inflammatory, autoimmune, ischemic, metabolic disorders, and cancers. Despite therapeutic advances, precise regulation of macrophage polarization remains challenging. Natural products have recently emerged as promising therapeutic regulators. Astragaloside IV (AS-IV) and its hydrolysate cycloastragenol (CAG), which are bioactive compounds derived from Astragalus membranaceus, have garnered significant interest due to their notable pharmacological properties encompassing anti-inflammatory, immunomodulatory, and antitumor effects. Nevertheless, the intricate multi-pathway mechanisms through which AS-IV and CAG regulate macrophage polarization are still not fully understood. A systematic review of literature from PubMed, Google Scholar, and SciFinder (2013–2025) shows that AS-IV and CAG modulate macrophage polarization. These compounds target critical signaling pathways, including TLR4/NF-κB, PI3K-AKT, AMPK, and PPARγ. These compounds exhibit therapeutic potential by suppressing pro-inflammatory M1 phenotypes and promoting anti-inflammatory/reparative M2 phenotypes. Their activities include anti-inflammatory, tissue-regenerative, and antitumor effects, with applications in inflammatory diseases, autoimmune disorders, ischemic vascular pathologies, metabolic syndromes, and cancer therapy. Furthermore, the integration of nanotechnology has emerged as a transformative approach to significantly enhance the bioavailability and targeted delivery of AS-IV and CAG, thereby expanding their clinical applicability. Despite the significant therapeutic potential of AS-IV and CAG in various disease models, their clinical translation remains constrained by low bioavailability. Future advancements that incorporate gene-editing technologies, computer-aided drug design, and nanotechnology are anticipated to optimize their pharmacokinetics and clinical efficacy. These innovations may position AS-IV and CAG as transformative agents in future therapies.